Penyelesaian Perhitungan pada Matching Saluran Transmisi λ/4 Menggunakan Pemrograman Berbasis Website - Viving Frendiana; Muhammad Teddy Rahmansyah (Politeknik Negeri Jakarta, 2021)
The matching circuit with a λ/4 transmission line, often called an impedance transformer λ/4, is a transmission line or waveguide with a 1/4 wavelength (φ) terminated by the load impedance. In many applications a condition of no reflection is desired at the transmission line connection. Therefore, to eliminate reflections due to differences in load impedance and wave impedance, impedance matching techniques are used. Impedance matching is carried out with the aim of matching the load impedance with the characteristic impedance on the transmission line so that the transmission line can be matched, so that the transmission process for a certain amount of power does not occur reflections which result in all transmitted power being absorbed. In this study, the completion of the λ/4 transmission line matching circuit was designed using website-based programming. The results of the simulation calculations using the website application obtained the impedance value on the transmission line with the λ/4 transformer according to the calculation of the mathematical equation. The matching process in this calculation requires a real load impedance.